2015
DOI: 10.1080/09593330.2015.1070922
|View full text |Cite
|
Sign up to set email alerts
|

Removal of steroid estrogens from municipal wastewater in a pilot scale expanded granular sludge blanket reactor and anaerobic membrane bioreactor

Abstract: Anaerobic treatment of municipal wastewater offers the prospect of a new paradigm by reducing aeration costs and minimizing sludge production. It has been successfully applied in warm climates, but does not always achieve the desired outcomes in temperate climates at the biochemical oxygen demand (BOD) values of municipal crude wastewater. Recently the concept of ‘fortification' has been proposed to increase organic strength and has been demonstrated at the laboratory and pilot scale treating municipal wastewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Concentrations of E1, E2, EE2 and E3 in the effluents from the UASB reactor and the HRAPs are shown in Figure 3. Removals < 50% were observed for E1 and E3 after the UASB treatment, which is in accordance with previous publications in anaerobic systems such as anaerobic membrane reactors and completed stirred tank reactors (Gonzalez-Gil et al, 2016;Ito et al, 2016). The low removal of E1 and E3 may be associated with the low HRT (7 hours) and the low sludge retention time (SRT) (20 days) applied in the UASB reactor.…”
Section: Estrogenssupporting
confidence: 89%
“…Concentrations of E1, E2, EE2 and E3 in the effluents from the UASB reactor and the HRAPs are shown in Figure 3. Removals < 50% were observed for E1 and E3 after the UASB treatment, which is in accordance with previous publications in anaerobic systems such as anaerobic membrane reactors and completed stirred tank reactors (Gonzalez-Gil et al, 2016;Ito et al, 2016). The low removal of E1 and E3 may be associated with the low HRT (7 hours) and the low sludge retention time (SRT) (20 days) applied in the UASB reactor.…”
Section: Estrogenssupporting
confidence: 89%
“…The removal percentages observed by Paterakis et al 13 were between 68 and 96% for estrone (E1) and 4-43% for 17 -ethinylestradiol (EE2) during anaerobic digestion of primary and mixed sewage sludge under mesophilic and thermophilic conditions. Ito et al 14 studied the removal of E1, estradiol (E2), estriol (E3) and estrone sulphate (E1-3S) in an anaerobic membrane bioreactor, and the removal percentages were 58% (E1), 77% (E2), 60% (E3) and 95% (E1-3S). These researchers concluded that estrogens could be removed effectively in an anaerobic reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of E1, E2, EE2 and E3 in the effluents from the UASB reactor and the HRAPs are shown in Figure 5.3. Removals < 50% were observed for E1 and E3 after the UASB treatment, which is in accordance with previous publications in anaerobic systems such as anaerobic membrane reactors and completed stirred tank reactors (GONZALEZ-GIL et al, 2016;ITO et al, 2016). The low removal of E1 and E3 may be associated with the low HRT (7 hours) and the low sludge retention time (SRT) (20 days) applied in the UASB reactor.…”
Section: Estrogenssupporting
confidence: 89%